Investigating the effect of local addition of hydrogen to acoustically excited ethylene and methane flames. (23rd April 2019) - Hussain, Taaha; Talibi, Midhat; Balachandran, Ramanarayanan
Abstract: While lean combustion in gas turbines is known to reduce NOx, it makes combustors more prone to thermo-acoustic instabilities, which can lead to deterioration in engine performance. The work presented in this study investigates the effectiveness of secondary injection of hydrogen to imperfectly premixed methane and ethylene flames in reducing heat release oscillations. Both acoustically forced and unforced flames were studied, and simultaneous OH and H atom PLIF (planar laser induced fluorescence) was conducted. The tests were carried out on a laboratory scale bluff-body combustor with a central V-shaped bluff body. Two-microphone method was used to estimate velocity perturbations from pressure measurements, flame boundary images were captured using high speed Mie scattering, while global heat release fluctuations were determined from OH* chemiluminescence. The results showed that hydrogen addition considerably reduced heat release oscillations for both methane and ethylene flames at all the forcing frequencies tested, with the exception of methane flames forced at 315 Hz, where oscillations increased with hydrogen addition. The addition of hydrogen reduced the extent of flame roll-up for both methane and ethylene flames, however, this reduction was larger for methane flames. NOx exhaust emissions were observed to increase with hydrogen addition for both methane and ethylene flames, with absolute NOx concentrations higher for ethylene flames, due to higher flame temperatures. Highlights: Local H2 addition to imperfectly premixed flames studied for the first time. Simultaneous OH and H atom PLIF carried out on forced turbulent flames. Comparison of effectiveness of H2 addition on methane and ethylene flames. H2 addition reduced magnitude of flame response. Larger reduction in flame response observed for methane in comparison to ethylene.